Analisis Pengelolaan Sampah di Kampus Universitas Negeri Jakarta sebagai Bagian dari Green Campus - Ria Resti Fauziah; Santoso Sri Handoyo; Anisah (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to examine waste management at Universitas Negeri Jakarta (UNJ) as part of the efforts to achieve a green campus. The focus of the research is on the waste indicator, which is assessed using the standards of the UI GreenMetric World University Rankings. The study also seeks to identify the actual conditions of waste management at UNJ, particularly within Campus A, so that the implementation of sustainable waste management can be comprehensively analyzed. The research employs a quantitative descriptive approach, with data collected through documentation and interviews with key informants, including cleaning supervisors, students, and campus management staff. The collected data were analyzed based on six waste management indicators from the UI GreenMetric (WS1-WS6), which include the 3R program (reduce, reuse, recycle), reduction in the use of paper and plastic, processing of organic and inorganic waste, hazardous waste (B3) management, and wastewater disposal. This analysis is supported by a description of the actual field conditions, including differences in information among informants, which reflect variations in understanding and implemetation across campus units.  The findings indicate that waste management at Campus A of UNJ has shown positive initiatives, especially in the indicator of reducing paper and plastic use (WS2), which achieved the maximum score. However, some indicators, such as inorganic waste processing (WS4) and hazardous waste (B3) management (WS5), still show low performance due to limited sorting facilities, a lack of awareness among the academic community, and uneven operational procedures across units. Overall, Campus A of UNJ obtained a score of 1,200 out of 1,800 in the waste category, indicating that the green campus implementation is underway, but it still requires strengthening in technical aspects, institutional management, and participation from the academic community in order to achive optimal sustainable waste amangement.